Modeling of ice dams in riverbeds (overview) - A. S. Tarasov (Лëд и снег, 2020)
The paper gives an overview of the main publications on the subjects of modeling of ice jams in riverbeds with an emphasis on the experience abroad. Different approaches to modeling of ice jams in rivers are considered conceptually together with a wide range of problems which are solved by means of the modeling. The most successful countries and scientific groups in this area of studies are identified and presented in the article. The most-used computer models were determined, and characteristics of them were investigated. When reviewing, the comparative-descriptive method was used. The list of leading publications on the above subjects was analyzed. Relevant literature was selected using the citation databases – RSCI (Russian Science Citation Index), Scopus and Web of Science. Final results of the work are as follows: a wide range of scientific publications on the subjects of the ice jam modeling published for the last 18 years (1999–2017) had been considered. The geography of publications extends from North America up to Eurasia and Japanese islands. A comparative table of the most commonly used computer models together with characteristics of them had been constructed. The most promising areas of development in the field of modeling of the ice jams are shown.